Code mixing in Denny Sumargo's podcast Study: sociolinguistics - Miftahie Fajriya Arbi; Mintowati (International Journal of Technology and Education Research, 2026)
This research is motivated by the widespread use of code-mixing in digital communication, particularly in podcast content on YouTube. This phenomenon indicates the use of two or more languages ​​in a single utterance, influenced by the speaker's bilingual abilities. This study aims to describe the forms, causal factors, and functions of code-mixing in Denny Sumargo's podcast with Raline Shah and Dilan Janiyar. This study uses a descriptive qualitative approach. The research population consists of all utterances in Denny Sumargo's podcast, while the research sample consists of utterances containing code-mixing in two podcast episodes. The research instrument was the researcher himself with the help of free listening and note-taking techniques. Data were analyzed using the matching method with the connecting and comparing and differentiating technique. The results of the study indicate two forms of code-mixing: internal code-mixing and external code-mixing. The main factor causing code-mixing is the identification of language varieties in relaxed and informal situations. The functions of code-mixing include emphasizing meaning, familiarizing the conversational situation, and adjusting the topic of conversation. The conclusion of this study shows that code-mixing in podcasts is a form of bilingual communication strategy that reflects social identity and modern communication styles in digital media.